INTEGRASI ILMU & AGAMA DALAM PENDIDIKAN: Studi Perbandingan Pemikiran Yudian Wahyudi Dengan Seyyed Hossein Nasr - Suwanto, Eko; Mijdal, Baha Shofa; sadari, Sadari (Asosiasi Dosen PTKIS Indonesia, 2026)
The thoughts of Yudian and Nasr have made significant contributions to formulating an integrative Islamic education curriculum, namely uniting general and religious sciences within a single epistemological system. Nasr emphasized the importance of “sacred science” as the foundation of education that integrates with the spiritual and metaphysical dimensions of humankind. Meanwhile, Yudian proposed a more contextual approach through the reconstruction of Islamic epistemology based on local Indonesian social and cultural realities, yet transcendentally spiritual. The curriculum resulting from this synthesis of thought not only bridges the science-religion dichotomy but is also relevant for application in the world of contemporary Islamic education. Relevance to Madrasahs, Islamic Boarding Schools, and Contemporary Islamic Schools. The concept of science-religion integration is highly relevant for application in Islamic educational institutions such as madrasahs, Islamic boarding schools, and contemporary Islamic schools. Pesantren, as traditional Islamic institutions, can adopt Nasr's ideas to strengthen the Sufi and traditional scientific dimensions. Madrasahs and contemporary Islamic schools can integrate Yudian's approach within the context of national curriculum policies and the strengthening of national character based on Islamic values. This aligns with the vision of national Islamic education, which emphasizes not only intellectual intelligence but also spiritual and moral excellence. Therefore, these institutions have a significant opportunity to become pioneers of holistic Islamic education in Indonesia, and even globally. Implementing the integration of science and religion in Indonesia faces serious challenges, such as the dominance of the secular paradigm in science, the limited number of teachers and lecturers who understand Islamic epistemology, and the resistance of a still-dualistic academic culture. However, significant opportunities also exist, particularly with the emergence of Islamic universities adopting an integrative approach, such as UIN Sunan Kalijaga and UIN Syarif Hidayatullah. Globally, Nasr's thinking has made a significant contribution to bridging the dialogue between Islamic and Western intellectual traditions. Meanwhile, Yudian offers a local approach responsive to national dynamics, serving as a model for the Islamic world. Therefore, strengthening collaboration between educational institutions, researchers, and policymakers is key to the successful realization of this integration.